2021
DOI: 10.1007/s11356-021-17122-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the environmental Kuznets curve between economic growth and chemical fertilizer surpluses in China: a provincial panel cointegration approach

Abstract: This study investigated the relationship between fertilizer nitrogen (N) and phosphate (P) surpluses and economic development on the regional level in China. With a balanced panel dataset covering 30 provinces of mainland China from 1988 to 2019, we employed panel cointegrating polynomial regression (CPR) analysis using fully modified OLS (FM-OLS) estimators. Our results suggested that all provinces exhibit a long-run cointegrated relationship between fertilizer surpluses and real per capita gross regional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The number of studies focusing on agrochemical consumption as an index of environmental degradation in the EKC framework is limited [2]. Despite the different sources of environmental degradation within the agricultural sector mentioned above, the extended use of pesticides entails significant risks for humans and the environment in general unless they are used with caution; in that case, numerous advantages have been reported.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies focusing on agrochemical consumption as an index of environmental degradation in the EKC framework is limited [2]. Despite the different sources of environmental degradation within the agricultural sector mentioned above, the extended use of pesticides entails significant risks for humans and the environment in general unless they are used with caution; in that case, numerous advantages have been reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, their use contributes not only to hunger reduction but also to food security sustainability [1]. Long-term studies have unveiled that pesticides are responsible for 40 to 60% of crop yields in temperate climates, like those of most EU countries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the government's strategy through the provision of subsidized fertilizers shows a strong role for the growth of agricultural inputs. At the regional level in China, panel data involving 30 provinces has proven to be very dependent on chemical fertilizers, which have a linear ratio to agricultural yields to increase per capita GDP in agriculture [73]. Fertilizer policy support is the main key in crop production and increasing agricultural welfare in China, Russia, Indonesia and India [74].…”
Section: Justificationmentioning
confidence: 99%
“…It is worth noting that X i includes two key inputs-irrigation costs and chemical fertilizer use. Some empirical literature has reported that there is a nonlinear relationship between the above two inputs and agriculture production [40,41]. Therefore, quadratic terms of irrigation costs and chemical fertilizer use were incorporated into the analysis.…”
Section: Econometric Modelmentioning
confidence: 99%